2016
DOI: 10.1002/bin.1444
|View full text |Cite
|
Sign up to set email alerts
|

A Progression to Transfer RIRD to the Natural Environment

Abstract: Response interruption and redirection has been shown to be effective for decreasing vocal stereotypy, but treatment effects in the natural environment have yet to be documented in the literature. A recent review indicated the paucity of studies that implemented response interruption and redirection during typically occurring activities or for sessions longer than 5-10 min. One method to promote generalization across settings may be stimulus control procedures. The purpose of the current study was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Also, occurrence of body and hand stereotypies did not appear to be affected by the sequence of conducting probe assessments. Given these equivocal findings and the results of prior RIRD research (Love et al, ; Martinez et al, ; Schumacher & Rapp, ), future studies should continue to evaluate the effects of different stimulus characteristics and saliency on multiple topographies of motor stereotypy when intervening with RIRD and how establishing stimulus control over stereotypy in multiple settings can be of practical value for care providers (Rapp, Patel, Ghezzi, O'Flaherty, & Titterington, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, occurrence of body and hand stereotypies did not appear to be affected by the sequence of conducting probe assessments. Given these equivocal findings and the results of prior RIRD research (Love et al, ; Martinez et al, ; Schumacher & Rapp, ), future studies should continue to evaluate the effects of different stimulus characteristics and saliency on multiple topographies of motor stereotypy when intervening with RIRD and how establishing stimulus control over stereotypy in multiple settings can be of practical value for care providers (Rapp, Patel, Ghezzi, O'Flaherty, & Titterington, ).…”
Section: Discussionmentioning
confidence: 99%
“…First, David engaged in body and hand stereotypies less frequently during intervention compared with baseline phases. Second, RIRD had a progressively stronger effect the longer David was exposed to the procedure, and stereotypy continued to decrease when RIRD was implemented in another setting (Martinez et al, ). Third, the study found that a moderate degree of stimulus control was achieved over body stereotypy although less evident with hand stereotypy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying caregivers' perceptions of procedural strengths and weaknesses should direct future studies to better address their concerns. This may be particularly important as researchers have been transitioning from highly controlled laboratory evaluations to more naturalistic environments (e.g., Colón & Ahearn, ; Giles, Swain, Quinn, & Weifenbach, ; Martinez, Betz, Liddon, & Werle, ; Sloman, Schulman, Torres‐Viso, & Edelstein, ). In certain public settings, parents and other caregivers may be less able to implement RIRD or to permit sound‐producing toys.…”
Section: Discussionmentioning
confidence: 99%